2018
DOI: 10.1080/09546634.2018.1468062
|View full text |Cite|
|
Sign up to set email alerts
|

Serum prolactin level in chronic urticaria: Is bromocriptine inducing remission in chronic urticaria?

Abstract: Serum PRL levels could not be considered as a marker of the disease activity in CU patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The effects of prolactin on CU during pregnancy remain largely unexplored, but Sabry et al (29) reported significantly higher serum prolactin levels in a subset of CU patients (positive autologous serum skin test, ASST) and its association with disease severity. In contrast, Soliman et al (30) did not find any relationship between serum prolactin levels and urticaria activity.…”
Section: Hormonal Changesmentioning
confidence: 84%
“…The effects of prolactin on CU during pregnancy remain largely unexplored, but Sabry et al (29) reported significantly higher serum prolactin levels in a subset of CU patients (positive autologous serum skin test, ASST) and its association with disease severity. In contrast, Soliman et al (30) did not find any relationship between serum prolactin levels and urticaria activity.…”
Section: Hormonal Changesmentioning
confidence: 84%
“…1 Conversely, CU activity and its treatments with medications such as firstgeneration antihistamines, may put burden on pregnant women and their fetuses. 1,[42][43][44] Pregnant women with CU have an impaired quality of life and may suffer from anxiety and depression. [45][46][47] Several skin eruptions in pregnancy must be differentiated from the diagnosis of CSU.…”
Section: Chronic Urticaria and Pregnancymentioning
confidence: 99%
“…59 Finally, the administration of cyclosporine in pregnant women should remain a second choice based on the risk-benefit ratio. 43…”
Section: Cyclosporinementioning
confidence: 99%